PENGARUH EFEKTIFITAS DEWAN KOMESARIS DAN KOMITE AUDIT TERHADAP TAX AGGRESSIVENESS - Mirna Dyah Praptitorini S (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
The existence of governance structure such as board ofcommissioners and audit committee implies a better monitoring functionon the financial reporting process that represent manager actions.Nevertheless, the quality of the monitoring function depends on howeffective the board and the audit committee perform their duties. Thisstudy examines how the effectiveness of the board of commissioners andaudit committee in a two tierboard structure influences the taxaggressiveness.This study develops a score for board and audit committeeeffectiveness by using a checklist which captures how the independence,activity, size, and competence characteristics are reflected in the board ofcommissioners and audit committe.Hypothesis testing is carried out byusing a multiple regression model of 105 observations (firm-year) withthe sample taken from manufacture companies listed on the IndonesianStock Exchange during t.Results of this study provide robust evidencethat a more effective board of commissioners and audit committee willdecrease tax aggressiveness.